Haptic vision, acoustic and navigation control in virtual reality game - Basori, Ahmad Hoirul (Penerbit UTM, 2007)
Virtual reality game (VRG) is a recent research focusing to combine entertainment aspect with educational aspect. One of VRG elements that is very important to explore the virtual world is navigation control since it stimulates interactivity and immersiveness. Therefore, a lot of research have been conducted to improve the control on characters navigation. Basically, the navigation is controlled by hardware like mouse, keyboard, joystick and the 3D input control like Nintendo Wii controller. All of these give new opportunity to create natural movement of virtual human character. This chapter will describe the method to collaborate haptic and audio to get better navigation control. Navigation control is also useful to help impaired people in recognizing objects, locating particular position, and exploring the details about object information (Sallnas et al. 2006). The navigation control is also helpful to assist communication in collaborative virtual environment (Sallnas et al. 2006; Aylett et al. 2005). Other researchers also proposed methods on how to solve navigation problems such as exploring virtual world, locating a place, changing a place, remembering visited location and identifying the current location (Abasolo et al. 2007).